The invention of the colonial Americas : data, architecture, and the Archive of the Indies, 1781-1844 - Hamann, Byron Ellsworth, 1972- (Getty Research Institute, 2022)
"The Invention of the Colonial Americas is an architectural history and media-archaeological study of changing theories and practices of government archives in Enlightenment Spain"--